The effect of application of oil palm empty fruit bunch compost on production and metal uptake of eggplant in tailings of post-tin mining land - Ismed Inonu; Deni Pratama; Fajar Indah Puspita Sari; Nanda Nusantary Suwardih (Brawijaya University, 2020)
Tailings of post-tin mining land have the potential to be cultivation fields for eggplant, but the problem from post-tin-mining land is the low essential nutrient and high metal contents. The quality of land needs to be improved by providing ameliorant such as oil palm empty fruit bunch compost. This research aims to determine the best dosage of oil palm empty fruit bunch compost to production and metal uptake of eggplant in post-tin mining land. This research was conducted from January to May 2019 in post-tin mining land, Dwi Makmur Village, Bangka. This research used a randomized block design with six treatments and four replications. Treatments consisted of organic fertilizer (control) of 15 t/ha(K0), oil palm empty fruit bunch compost 20 t/ha(K1), 30 t/ha(K2), 40 t/ha(K3), 50 t/ha(K4), and 60 t/ha(K5). The results showed that the application of oil palm empty fruit bunch compost of 60 t/ha was the best dose to increase eggplant production in the tailing of post-tin mining land. Application of oil palm empty fruit bunch compost reduced metal absorption of eggplant fruit in tailing of post-tin mining land.